APPLICATION OF ASSOCIATIVE METHOD IN THE ACQUISITION OF ENGLISH VOCABULARY - Kuldosheva Nigora Shamsiddin qizi (Western European Studies, 2024)
Vocabulary serves as the basis of any language learning. To many learners of nonEnglish majors it is difficult to memorize English words. This paper defines associative method in presenting new terms to them. It is stated that associative method is receiving better outcomes both in short-term and long-term retention of English words. Compared to the traditional way, associative method turns out to be more efficient in the retention and memorization of new words. In addition, the differences appeared to be very significant in revision of words through making associations . Therefore, teachers have to encourage learners to review what they cover in class frequently, and learners themselves should try to participate actively in associative learning process
Keywords: English vocabulary teaching; associative method; traditional way